Knowledge of Traumatic Brain Injury among Educators. Issue 2 (2nd April 2016) - Ernst, William J.; Gallo, Adrienne B.; Sellers, Amanda L.; Mulrine, Jessica; MacNamara, Luciana; Abrahamson, Allison; Kneavel, Meredith
ABSTRACT: The purpose of this study is to determine knowledge of traumatic brain injury among educators. Few studies have examined knowledge of traumatic brain injury in this population and fewer still have included a substantial proportion of general education teachers. Examining knowledge of traumatic brain injury in educators is important as the vast majority of children with traumatic brain injury will return to school and many are likely to require support in the short term and some will require special education services in the long term. The Common Misconceptions of Traumatic Brain Injury questionnaire was completed by 94 educators. Participants demonstrated accurate knowledge on a number of questionnaire items associated with the identification of individuals with traumatic brain injury, common socio-emotional effects, and recovery from traumatic brain injury; however, a considerable degree of uncertainly was indicated on several items relevant to the school setting. In addition, substantial misconception rates were noted on only four items including one pertaining to recovery and another concerning the likelihood of additional brain injuries. Knowing someone with traumatic brain injury, participating in training and having taught a student with traumatic brain injury resulted in greater knowledge. Implications of these findings for educators are discussed.